The whole-brain child [compact disc, unabridged] : 12 revolutionary strategies to nurture your child's developing mind - Siegel, Daniel J., 1957- (Brilliance Audio, 2012)
Daniel J. Siegel Tina Payne Bryson demystify the meltdowns and aggravation, explaining the new science of how a child's brain is wired and how it matures. Complete with clear explanations, age-appropriate strategies for dealing with day-to-day struggles, and illustrations that will help parents explain these concepts to their children.